AKTIVITAS NUMERASI SISWA PADA PROSES DISKUSI DITINJAU DARI PEMOSISIAN SISWA KELAS V SD - Dyah Triwahyuningtyas; Herliani Eka Saputri; Nyamik Rahayu Sesanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Students' numeracy skills in group learning often show variations in roles that can affect the learning process and outcomes. This study aims to analyze the numeracy activities of fifth-grade students in group discussions, focusing on the roles of expert, facilitator, and novice. This study uses a descriptive qualitative approach with data collection through numeracy tests, non-participatory observation, and semi-structured interviews. Data validity was ensured through triangulation techniques. The results showed that students' numeracy skills were generally high, although some students still had difficulty in applying mathematical symbols correctly. Students' positions in the group influenced their numeracy achievement, with students acting as experts understanding the questions more quickly and leading the discussion, facilitators maintaining the flow of the discussion and encouraging participation, and beginners requiring more guidance. Interactions between positions contributed significantly to the improvement of numeracy skills, with the roles of experts and facilitators being the dominant factors. These findings provide a deeper understanding of the social dynamics in numeracy learning and recommend the application of positioning-based learning strategies to improve the effectiveness of discussions and student learning outcomes.